Issues in Healthcare Supply Chain Management: From Literature to Practice - Jessica Ricão Braga Da Conceição; Thaís Spiegel; Ana Carolina Pereira de Vasconcelos Silva; Augusto da Cunha Reis (International Journal of Supply Chain Management, 2020)
This research aims to identify the main issues on healthcare supply chain management literature, to analyze a real healthcare unit supply chain. The results are a framework compiling literature review, that allowed designing the medicines and materials supply chain of a network of hospitals in Brazil. The method consisted in conducting the literature review, describing the actual model of the healthcare units, using process management approach, such as value-added chain representation, and designing the new supply chain, adopting Lean Healthcare tools, such as A3 to guide the analysis and problems solution. The study demonstrates that the literature lacks healthcare supply chain management, since most articles have a pharmaceutical or care bias. Thus, this article contributes with an applied experience, which benefits both literature and organizational practice.